Analisis Isi Penyampaian Pesan Dakwah Toleransi Log-in Melalui Podcast Youtube Deddy Corbuzier - Anisa, Ayu; Suryasuciramdhan, Arfian; Zulfikar, Meiby; Dwiyanti, Shafira; ., Suminah (CV. ITTC INDONESIA, 2024)
Da'wah can be interpreted as a process of conveying or inviting someone consciously to embrace, study, and practice religious teachings, so as to awaken, restore the potential benefits of others that literally every human being should have. (Hilmi Sha'bani et al., 2024). Rapid technological development, the delivery of da'wah is intensively carried out through social media such as YouTube. Its broad scope of messages can be conveyed by reaching out to many masses from different cultures and religions. The author tries to